Optimizing the geothermal potential of tunnel water by separating colder sectional discharges - Case study Brenner Base Tunnel. (February 2023) - Geisler, T.; Wolf, M.; Götzl, G.; Burger, U.; Cordes, T.; Voit, K.; Straka, W.; Nyeki, E.; Haslinger, E.; Auer, R.; Lauermann, M.; Pol, O.; et al.
Abstract: The use of geothermal energy from tunnels offers an environmentally friendly option for heating and cooling of buildings in the vicinity of the tunnel structure. In the research project "Thermocluster", the geothermal potential of the Brenner Base Tunnel (BBT) was analysed and the utilization of the low-temperature heat to the city of Innsbruck was evaluated. A possible optimization on the geothermal performance was explored by separating colder sectional discharges from the total tunnel water drainage system. Further, the use of decentralized and centralized heat pumps, as well as heat distribution with different district heating networks (local low temperature heating and cooling networks, low-temperature network, classic district heating network), was investigated using process simulation. The results indicate that an optimization of the temperature of a subset of the total tunnel water discharge is possible. Furthermore, it could be shown that wide fluctuations in the efficiency of the heat pump can be expected. In addition, a rough cost estimation regarding the installation and distribution costs of the tunnel heat with different heat network variants is provided. This shows that the variant using decentralized heat pumps in the buildings and distribution via an anergy network is the most favourable in terms of installation. Highlights: Geothermal usage of tunnel heat in Austria. Analysis of the geothermal potential and optimization. Simply measures to increase the geothermal potential. Performance estimation of heat pumps using tunnel heat.